Strategi Penerjemahan Kata Zina dan Rafas: Sebuah Reinterpresentasi - Fahmi Gunawan (Badan Pengembangan dan Pembinaan Bahasa, 2022)
While a growing body of research on translation strategy produced by novice translators have been undertaken by many scholars, there is a paucity of research on 'zina' and 'rafas' translation strategy from Arabic to Indonesian. To fill this lacuna, the present study aims to analyze novice translators strategy for rendering the words zina and rafas and why they used it. The present study adopted translation process research design and translation strategy theory proposed by Gambier (2010). The findings demonstrate that the meaning of adultery is not restricted to